Views______By This River - ALEKSANDER RACZYŃSKI (Images)
Presented pictures are part of longer series. They were taken in many different places. My photographs help me to understand the world and myself. I do not follow any specific topic but I do believe in being able to communicate without it. My life and my photography are both a constant confrontation with my emotions. They make me feel closer to my soul and to the nature. I find it very helpful as what scares me the most is the lack of emotions.